Rib stress fractures and a novel muscle-sparing rib fixation plating in an elite tennis player: A systematic review of the literature and case report - Fearing, M.; Behzadpour, V.; House, R. D.; Tarakemeh, A.; Morey, T.; Randall, J.; Vopat, B. (Sports Health: A Multidisciplinary Approach, 2024)
A nationally ranked Division One female collegiate tennis player presented with pain in the chest and right posterior rib region after feeling a popping sensation during a routine overhead movement. The patient was eventually diagnosed with 2 lower rib stress fractures. After unsuccessful conservative management, the player underwent an open reduction and internal fixation and autologous bone grafting of the sixth and seventh ribs with a muscle-sparing approach and was able to return to full competition. We present this case along with a systematic review of the literature regarding rib stress fractures, which included 6 separate online data sources (PubMed, EMBASE, Cochrane, CINAHL, SportDiscus, and Medline). The successful surgical intervention demonstrates a significant option for elite athletes who wish to return to competition but have been unable to with standard of care conservative management of rib stress fractures.